2021
DOI: 10.1186/s12864-021-07466-9
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal testosterone triggers long-term behavioral changes in male zebra finches: unravelling the neurogenomic mechanisms

Abstract: Background Maternal hormones, like testosterone, can strongly influence developing offspring, even generating long-term organizational effects on adult behavior; yet, the mechanisms facilitating these effects are still unclear. Here, we experimentally elevated prenatal testosterone in the eggs of zebra finches (Taeniopygia guttata) and measured male aggression in adulthood along with patterns of neural gene expression (RNA-seq) and DNA methylation (MethylC-Seq) in two socially relevant brain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Using previously developed microdissection protocols (Horton et al . 2020), we conducted transcriptome-level sampling of the pituitary, testes, and 10 brain nuclei comprising the entire SBN and a portion of the mesolimbic reward system (MRS) (Lopes and König 2020; Bentz et al . 2021b; Kabelik et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using previously developed microdissection protocols (Horton et al . 2020), we conducted transcriptome-level sampling of the pituitary, testes, and 10 brain nuclei comprising the entire SBN and a portion of the mesolimbic reward system (MRS) (Lopes and König 2020; Bentz et al . 2021b; Kabelik et al .…”
Section: Resultsmentioning
confidence: 99%
“…Using the most comprehensive transcriptome-level sampling of the SBN to-date (Lopes and König 2020; Bentz et al . 2021b; Kabelik et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, J o u r n a l P r e -p r o o f Bentz et al showed that zebra finches from testosterone-injected eggs presented more aggressive behaviours than control males, and had several differentially expressed genes that were also differentially methylated. Their findings suggest that in ovo testosterone may induce epigenetic modifications that could influence aggression behaviour (Bentz et al, 2021).…”
Section: Effects Of Pms On the Histone Post-translational Marks In F1...mentioning
confidence: 99%
“…To mimic the effects of PMS, eggs of zebra finches were previously injected with testosterone which lead to different expression of hundreds of genes particularly in the hypothalamus (Bentz et al, 2021). Some authors suggested that influences of PMS on epigenetic marks could be implicated in offspring behavioural changes J o u r n a l P r e -p r o o f including more hypotonia and lethargy (human: Conradt et al, 2013), modulations of locomotor activity (rat: Mychasiuk et al, 2011), greater fearfulness (human: Ostlund et al, 2016), poorer spatial learning abilities (mice: Benoit et al, 2015), more aggressive behaviour (zebra finches: Bentz et al, 2021) or different foraging strategies (chicken: Nätt et al, 2009). Birds, especially precocial, are ideal animal models to study and understand these phenomena.…”
Section: Introductionmentioning
confidence: 99%